TRANSFORMATIONS IN A LITTLE PRINCESS MOVIE: AN ADAPTATION ANALYSIS - L Dyah Purwita Wardani; Fina Rifqiyah; Dina D. Kusumayanti (Universitas Nahdlatul Wathan Mataram, 2021)
A Little Princess is a novel written by Frances Hodgson Burnett (1905). This novel has been adapted several times into film, one of which is Alfonso Cuaron's (1995) work produced by Warner Bross Picture. This film was released in 1995 with the same title,